2020
DOI: 10.1128/jvi.00454-20
|View full text |Cite
|
Sign up to set email alerts
|

The Andes Orthohantavirus NSs Protein Antagonizes the Type I Interferon Response by Inhibiting MAVS Signaling

Abstract: The small messenger RNA (SmRNA) of the Andes orthohantavirus (ANDV), a rodent-borne member of the Hantaviridae family of viruses of the Bunyavirales order, encodes a multifunctional nucleocapsid (N) protein and for a nonstructural (NSs) protein of unknown function. We have previously shown the expression of the ANDV-NSs, but only in infected cell cultures. In this study, we extend our early findings by confirming the expression of the ANDV-NSs protein in the lungs of experimentally infected golden Syrian hamst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 94 publications
(175 reference statements)
0
29
0
Order By: Relevance
“…Only a few studies have suggested a role of hantaviral NSs in IFN antiviral response [ 21 ]. A recent study described the detection of ANDV NSs in lungs of infected Syrian hamsters used as model of pathogenesis, and it has shown that ANDV NSs antagonizes the IFN-I signaling pathway by disrupting MAVS-TBK1 interaction [ 60 ]. It has been published that PUUV deficient for NSs expression was 10 times less infectious in A549 interferon competent cells than the wild-type virus strain [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Only a few studies have suggested a role of hantaviral NSs in IFN antiviral response [ 21 ]. A recent study described the detection of ANDV NSs in lungs of infected Syrian hamsters used as model of pathogenesis, and it has shown that ANDV NSs antagonizes the IFN-I signaling pathway by disrupting MAVS-TBK1 interaction [ 60 ]. It has been published that PUUV deficient for NSs expression was 10 times less infectious in A549 interferon competent cells than the wild-type virus strain [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, Type I IFNs can bind to IFNAR2, and then recruit IFNAR1, and consequently form a signaling-competent ternary complex to activate the heterotrimeric transcription factor complex interferon-stimulated gene factor 3 (ISGF3), which is comprised of phosphorylated signal transducer and activator of transcription (STAT)1 and STAT2 and interferon regulatory factor 9 (IRF9), through the Janus kinase (JAK)-STAT signal pathway [ 31 , 32 , 33 ]. The activated ISGF3 can translocate to the nucleus and bind to IFN-stimulated response elements (ISREs) in the upstream promoter regions of ISGs [ 34 , 35 ] and then encode the numerous proteins with potent antiviral activities [ 18 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…9 Upon viral infection, pathogen-associated molecular patterns are recognized by host cell receptors at extra-and intracellular levels as Toll-like receptors (TLR), retinoic acid-inducible gene I (RIG-I), melanoma differentiation-associated protein 5 (MDA5) and protein kinases (PKR). [69][70][71][72][73][74][75][76] TLR3 recognizes the double-stranded RNA (dsRNA) viral replication intermediate, promoting the synthesis of alpha/beta interferon (IFN-a/b) and interferon-stimulated genes (ISGs) to fight the viral infection. 69 Nevertheless, pathogenic hantaviruses apparently alter the activation of TLR3 and its downstream effectors.…”
Section: Hantavirus Recognition By Innate Immunitymentioning
confidence: 99%